Pretreatment of sweet sorghum stalk with aqueous hydrogen peroxide for enhancing methanolysis and property of the bio-oil. (September 2021) - Li, Zhan-Ku; Cheng, Jin-Yuan; Yan, Hong-Lei; Yan, Jing-Chong; Lei, Zhi-Ping; Ren, Shi-Biao; Wang, Zhi-Cai; Kang, Shi-Gang; Shui, Heng-Fu
Abstract: Alcoholysis is a promising approach for converting biomass into fuels and/or chemicals under mild conditions. However, the effect of pretreatment on biomass alcoholysis was rarely reported. Herein, the effect of pretreatment with H2 O2 on sweet sorghum stalk (SSS) methanolysis was examined. The results show that the pretreatment could markedly improve the bio-oil (BO) yield and decrease the appropriate temperature for obtaining maximum BO yield. The appropriate temperature for pretreated SSS methanolysis was determined to be 280 °C and the maximum BO yield is 44 wt%. In addition, higher heating values of the BOs were also enhanced based on elemental analysis. According to analysis with gas chromatograph/mass spectrometer, phenolic compounds, esters, and sugars are predominant in the BOs, and the yield of phenolic compounds significantly increased from 91.75 to 111.68 mg . g −1 by the pretreatment. Moreover, polar species in the BOs decreased and deoxygenation occurred during pretreated SSS methanolysis. Analyses with scanning electron microscope and N2 physisorption reveal that pretreated SSS has more grooves and higher specific surface area and anomalous porosity than SSS. According to analyses with Fourier transform infrared spectrometer and X-ray photoelectron spectrometer, oxygen functional groups mainly in the forms of CO and COO were introduced into SSS by the pretreatment. The changes of physical and chemical structures should be responsible for enhancing SSS methanolysis and property of the BO. Highlights: Yield and property of BO obtained from SSS methanolysis improved by pretreatment with H2O2. The appropriate temperature for obtaining maximum BO yield decreased by the pretreatment. Physical structure change results in more efficient penetration of methanol into SSS. Oxygen functional groups mainly in the forms of CO and COO were introduced into SSS.